Til sammenligning: En retorisk tilgang til intertekstualitet - Kraglund, Rikke Andersen (K&K - Kultur og Klasse, 2019)
Generally, the conception of intertextual references in literary theory has been either very broad or very narrow and detail-oriented. On the one hand, Roland Barthes and Julia Kristeva conceive of intertext as a universal feature of all texts. No text is original and made by itself isolated from those existing before it. All texts, in short, are intertexts because they refer to other texts, conventions, and presuppositions beyond authors’ intentions. But this broad concept is difficult to work with in analyzing works of literature. It poses problems of identification and does not mark out a manageable area of investigation or object of attention with the undefined and infinite discursive space it designates and its idea about anonymous citations. Generally, the conception of intertextual references in literary theory has been either very broad or very narrow and detail-oriented. On the one hand, Roland Barthes and Julia Kristeva conceive of intertext as a universal feature of all texts. No text is original and made by itself isolated from those existing before it. All texts, in short, are intertexts because they refer to other texts, conventions, and presuppositions beyond authors’ intentions. But this broad concept is difficult to work with in analyzing works of literature. It poses problems of identification and does not mark out a manageable area of investigation or object of attention with the undefined and infinite discursive space it designates and its idea about anonymous citations. On the other hand, we have the more restricted view that focuses on specific, readily recognized signs of intertextual relations between literary texts. Gérard Genette offers a vocabulary to describe the interaction between only two identifiable texts. In this article, I shall propose a third alternative that takes the middle ground and investigate what a rhetorical approach to intertextuality means for the understanding of the concept of comparison.